The Aesthetic Items Scale: A Tool for the Evaluation of Aesthetic Outcome after Breast Reconstruction - Dikmans, Rieky E.G. (Plast Reconstr Surg Glob Open, 2017)
BACKGROUND: Valid tools to assess aesthetic outcomes after breast reconstructive surgery are scarce. Previously a professional aesthetic assessment scale was introduced, the Aesthetic Items Scale (AIS). We aim to determine if this method is a valid and reliable tool to assess aesthetic outcome after breast reconstructive surgery. METHODS: The study population was consenting women who underwent prophylactic mastectomy with subsequent implant-based breast reconstruction. The aesthetic outcome with regard to breast volume, shape, symmetry, scars, and nipple areola complex was rated on a 5-point scale using standardized photographs to give a summed total score. Photographs were evaluated by the patient, 5 plastic surgeons, and 3 mammography nurses. An overall rating of aesthetic outcome on a 1–10 scale was given separately. We determined the intraclass correlation coefficient and assessed interobserver agreement. To assess validity, we calculated the correlation between total score and overall rating of aesthetic outcome. RESULTS: Interobserver reliability was highest between plastic surgeons for the subitem and overall scores and ranged between 0.56 and 0.82. The summed score of the AIS correlates strongly with the overall rating in professionals but not in patients. CONCLUSIONS: The AIS is a valid and reliable method for evaluating aesthetic outcome of breast reconstruction by plastic surgeons. The results indicate that patients judge aesthetic outcome differently, taking into account factors that are not represented in the AIS. Professionals can use this method to evaluate surgical results, but other measurements are needed to map satisfaction of the patient with her breasts.